Evaluasi Kinerja Portofolio Menggunakan Strategi Pasif VS Strategi Aktif - , Tetty Widayantie ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Many investment alternatives that can be chosen by the investors in developing their funds. Capital market is a long-term investment alternative. Investing basically aims to gain return, but investors should also bear the risks of the embedded investment. To overcome or reduce risk, investors can make diversity through portfolio establishment. Formatting a stock portfolio can be divided into 2 (two) strategies, portfolio establishment by using passive strategy (following LQ 45 index) and active strategy (selecting stocks with certain criteria). This research aimed to determine the return and risk of both strategies. In addition, it will also be compared between return and risk produced, is there any noticeable difference or not. Processing data in this research was taken from the data in 6 (six) years, from 2005 to 2010 which formed 22 (twenty two) portfolios then, they were 11 (eleven) active and passive portfolios. Passive portfolio was formed by following portfolio of LQ 45 index, while the active portfolios were formed by certain criteria. In this research the formation of active portfolios were by selecting stocks which have over 0.15% of weighted index and have positive growth in each semester. After active portfolios were formed, weighted was done. Weighting was done by using calculation of unweighted stock index (Unweighted Price), meaning that all stock/share have same scale without considering the price of current stock/share (capitalization) to do the calculation of the index. After going through the stages in the formation and measurement of performance (return and risk), gained the result that from 11 (eleven) passive portfolios, there were only 3 (three) passive portfolio returns better than the market returns. Meanwhile, from 11 (eleven) active portfolios, there were 6 (six) active portfolio returns better than the market returns. For evaluating the performance of these two strategies, it was used 3 (three) measurements such as Sharpe Index, Treynor Index and Jensen Index. In Shape Index and Index of Jensen measurement, there were not any significant differences between passive and active portfolios (H0 is accepted), while for the Treynor Index measurement there were significant differences between the performance of passive and active portfolios (H0 is rejected).